The impact of long-term CO2 enrichment on sun and shade needles of Norway spruce (Picea abies): photosynthetic performance, needle anatomy and phenolics accumulation - Lhotáková, Zuzana; Urban, Otmar; Dubánková, Marianna; Cvikrová, Milena; Tomášková, Ivana; Kubínová, Lucie; Zvára, Karel; Marek, Michal V; Albrechtová, Jana (Plant science, 2012)
Norway spruce (Picea abies L. Karst) grown under ambient (365-377 μmol(CO(2)) mol(-1); AC) and elevated (700 μmol(CO(2)) mol(-1); EC) CO(2) concentrations within glass domes with automatically adjustable windows and on an open-air control site were studied after 8 years of treatment. The effect of EC on photosynthesis, mesophyll structure and phenolics accumulation in sun and shade needles was examined. Photosynthetic assimilation and dark respiration rates were measured gasometrically; the structural parameters of mesophyll were determined using confocal microscopy and stereological methods. The contents of total soluble phenolics and lignin were assessed spectrophotometrically, and localizations of different phenolic groups were detected histochemically on needle cross-sections. EC enhanced the light-saturated CO(2) assimilation rate and reduced dark respiration in the current-year needles. No effects of CO(2) enrichment on mesophyll structural parameters were observed. Similarly, the accumulation and localization of phenolics and lignin remained unaffected by EC treatment. Needles differentiated into sun and shade ecotypes in the same manner and to the same extent irrespective of CO(2) treatment. Based on these results, it is apparent that the EC-induced enhancement of photosynthesis is not related to changes in the examined structural parameters of mesophyll and accumulation of phenolic compounds.
Keywords: Lignin; fenoly; ekotyp; Ecotype; mezofylové buňky; lignin; Photosynthesis; oxid uhličitý; Plant Leaves; Phenols; Trees; Carbon Dioxide; fotosyntéza; Mesophyll Cells; sluneční záření; Time Factors; Picea; smrk; stromy; časové faktory; Sunlight; listy rostlin